Climate Change And The Truth Behind Data - Mouzouropoulos, Theseas (My University, 2023)
CLIMATE CHANGE AND THE TRUTH BEHIND DATA: Form follows data and follow the data and form will rise to meet you. The poster is a visualization of the global land and ocean temperature anomalies from 1856–2023. By doing so, we can see the obvious truth behind data and climate change: global ocean surface temperature during this January–July 2023 period ranked second warmest on record.
Keywords: Graphic Design; poster design